OntoMP, an ontology to build the museum of the person - Martini, Ricardo G. (2016)
This paper is concerned with the creation of a specific ontology for the knowledge repository of the Museum of the Person (Museu da Pessoa). The Museum of the Person assets are composed of several interviews (collected previously for a large cultural project) involving common people, to perpetuate their life stories. The museum holds an heterogeneous collection of XML documents. In such format, the collection items are many times not recognizable and understandable by the visitors who wish to explore it. Therefore, we intend to use an ontology that allows a conceptual navigation over the available information, enabling the visitors to extract knowledge during the visit to these life stories. So, this paper aims at presenting the ontology we have developed using CIDOC Conceptual Reference Model (CIDOC-CRM)[1] to enable visitors to lookup individual life stories, read them, and also intercross information among a cluster of life stories to build up the story of a company/institution or to study social behaviors and customs.